Rancang Bangun Online Shop pada Toko Indo Bed Cover Jambi - wati, nila nila (Lembaga Penelitian Dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2017)
The need for devices that use information technology to improve the performance of a system to encourage every company seeks to build a system that can facilitate its performance and improve its service to the general public. Writing this paper describes the stages of the building an Online Store or Online Shop in Toko Indo Bed Cover Jambi which aims to facilitate Toko Indo Bed Cover Jambi in promoting its products, as well as facilitate the consumers or customers in making reservations and purchase goods using online media. This information system is built using Macromedia Dreamweaver CS5 and MySQL database relating to research obtained through field studies and literature.   Keywords : Online Shop, Promotional, Booking, Bed Cover, Macromedia Dreamweaver CS5, and MySQL.